Conceptual similarities; distinct difference: exploring ‘the gang’ in mainland China - Atkinson-Sheppard, Sally (The British journal of criminology, 2019)
This article discusses the ‘gang’ in Mainland China. By drawing on extensive observation, 99 qualitative interviews with criminal justice practitioners, NGO workers, academics, journalists, diplomats, community members and young people associated with gangs. The article considers the ways in which gangs are conceptualized in mainland China. The article uses the framework of ‘conceptual similarities and distinct difference’ to consider the ways in which Chinese gangs are similar to their counterparts around the world, but also how they differ. The article concludes by reflecting on the implications of this for law, legislation, policy and practice as well as global understandings of gangs and organized crime.